2020
DOI: 10.3390/polym13010051
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Modified Highly Biocompatible Bacterial-poly(3-hydroxybutyrate-co-4-hydroxybutyrate): A Review on the Promising Next-Generation Biomaterial

Abstract: Polyhydroxyalkanoates (PHAs) are bacteria derived bio-based polymers that are synthesised under limited conditions of nutritional elements with excess carbon sources. Among the members of PHAs, poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [(P(3HB-co-4HB)] emerges as an attractive biomaterial to be applied in medical applications owing to its desirable mechanical and physical properties, non-genotoxicity and biocompatibility eliciting appropriate host tissue responses. The tailorable physical and chemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 129 publications
0
9
0
Order By: Relevance
“…Polyhydroxyalkanoates (PHAs), a family of fermentation derived biodegradable polyesters, have received extensive attention 14,15 . There are more than 150 PHA species, such as poly (3‐hydroxybutyrate‐ co ‐3‐hydroxyvalerate) (PHBV), 16 poly[(R)‐3‐hydroxybutyrate‐ co ‐4‐hydroxybutyrate] (P34HB), 17 and so forth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyhydroxyalkanoates (PHAs), a family of fermentation derived biodegradable polyesters, have received extensive attention 14,15 . There are more than 150 PHA species, such as poly (3‐hydroxybutyrate‐ co ‐3‐hydroxyvalerate) (PHBV), 16 poly[(R)‐3‐hydroxybutyrate‐ co ‐4‐hydroxybutyrate] (P34HB), 17 and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…10 Polyhydroxyalkanoates (PHAs), a family of fermentation derived biodegradable polyesters, have received extensive attention. 14,15 There are more than 150 PHA species, such as poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), 16 poly[(R)-3-hydroxybutyrate-co-4-hydroxybutyrate] (P34HB), 17 and so forth. In our previous work, we have found that a high content of PHBV (PHBV content ≥ 30 wt.%) could significantly improve the heat resistance of the PLA fibers.…”
mentioning
confidence: 99%
“…56 Some studies based on P34HB were conducted for bone tissue engineering with various types of scaffold structures not formed using 3D printing techniques, 57 and weak osteogenic effects were observed due to the hydrophobicity of P34HB, which is preferred for cellular adhesion, migration and differentiation. 58 Therefore, the hydrophilicity of the PDA coating alters the surface physical properties of P34HB (Fig. S2 and S3, ESI †), which changes the cell behaviors in the scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…PHB shares similar properties with PP, in areas such as tensile modulus, tensile strength, and melting temperature. However, PHB is biodegradable and biocompatible, and its degradation does not release toxic products, which does not occur with PP [ 47 ]. The above characteristics would make PHB suitable to replace the use of PP in the industry.…”
Section: Phb Properties and Applicationsmentioning
confidence: 99%
“… PHB granules in bacteria. Granules contain growing PHB chains at the core and are surrounded by GAPs (Created with data previously reported [ 39 , 43 , 47 ]). …”
Section: Figurementioning
confidence: 99%